2011
DOI: 10.1002/acr.20428
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined influence of homeownership, occupation, education, income, and community poverty on physical health in persons with arthritis

Abstract: Objective. To examine the independent and combined influence of individual-and community-level socioeconomic status (SES) measures on physical health status outcomes in people with self-reported arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
5
20
0
Order By: Relevance
“…These results suggest that education and community poverty are more important SES predictors of hip OA measures than occupation. This finding is supported by a previous study which showed that only income and education remained significant predictors of physical health in persons with self-reported arthritis (37). It has been suggested that community-level SES measures may provide further information that is not captured by individual-level measures alone (29).…”
Section: Discussionsupporting
confidence: 86%
“…These results suggest that education and community poverty are more important SES predictors of hip OA measures than occupation. This finding is supported by a previous study which showed that only income and education remained significant predictors of physical health in persons with self-reported arthritis (37). It has been suggested that community-level SES measures may provide further information that is not captured by individual-level measures alone (29).…”
Section: Discussionsupporting
confidence: 86%
“…This study confirmed previous findings in rheumatology research that neighborhoods have an independent effect on outcomes in arthritis [30,31,46]; independent associations were noted between neighborhoods with higher rates of household poverty and outcomes of knee radiographic OA, bilateral knee radiographic OA and symptomatic knee OA in the Johnston County Osteoarthritis Project (Table 2) [40]. A recent multilevel Australian study using self-report measures of arthritis also found independent associations of neighborhood disadvantage with prevalence of arthritis such that residents of the most disadvantaged neighborhoods were 42% more likely than those in the least disadvantaged neighborhoods to self-report arthritis [38].…”
Section: Studies Of Social Determinants and Oa Outcomessupporting
confidence: 92%
“…Evidence exists linking lower levels of individual socioeconomic status (SES) and poorer health outcomes in many diseases [2327], including arthritis [28–31]. Recent data suggest that the social context (i.e., factors in society that cannot be directly measured at the individual level), or socioeconomic environment of an individual’s neighborhood may be relevant to arthritis prevalence and health outcomes as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Expert opinion varies widely on what constitutes a meaningful difference and its assessment. Our group has previously calculated quasi-effect size for health status [64] to better interpret results. We similarly calculated quasi-effect size for physical functioning, disability, helplessness, and mental health by standardizing the parameter estimates by corresponding standard deviations in this study.…”
Section: Discussionmentioning
confidence: 99%